Factors Critical for Learning Management System in On-line Distance learning (ODL) - Zurinah, Suradi; Nazatul Shima, Abdul Rani; Nurziyanti, Mohamad Khan (2013)
Abstract On-line distance learners depend heavily on learning management system (LMS) to fulfill their learning requirements. The learners would expect that LMS will contain all the necessary learning materials and resources for learners to refer to for learning. Also, the system should be able to support such activities like downloading, uploading, forming, and chatting. Once the system is established, learners would use the system provided if they are satisfied with it and in turn increases learners retention. Hence, this paper is to examine the factors affecting the e-satisfaction and e-retention of a learning management system (LMS). The factors identified include: technology acceptance model, perceived quality, and LMS characteristics. Keywords Learning Management System, On-line Distance Learning, E-Learning, Adult Learner and Malaysia